Clinical profile of dengue fever and coinfection with chikungunya - Jitendra Singh; Anju Dinkar; Rana Gopal Singh; Mohammad Si Siddiqui; Nikhil Sinha; Sanjiv Kumar Singh (Tzu Chi Medical Journal)
Objective: Arthropod-borne viral diseases are a major burden on the health-care system worldwide. Only a few studies have reported on coinfection of dengue fever (DF) with the chikungunya virus in North India. We investigated the seroprevalence and significance of the clinicobiochemical profile of dengue and chikungunya coinfection. Besides this, the authors try to emphasize rationalize platelets transfusion. Material and Methods: The present study was conducted at the Heritage Institute of Medical Science, Varanasi, India, from July to December 2016. A total of 1800 suspected cases with acute viral febrile illness (age >18 years) were investigated to exclude other causes of acute febrile illnesses. Of these, 121 patients (6.72%) were diagnosed as seropositive for dengue and chikungunya mono or coinfection using IgM ELISA and were included in the study. Results: The male gender was predominant. The majority were in the 20–30-year age group with cases peaking in November. There were 102 (84.29%) cases of dengue, 6 (4.95%) cases of chikungunya, and 13 (10.74%) cases positive for coinfection. Fever was present in all cases. Headache followed by nausea/vomiting and generalized weakness were the most common symptoms in patients with DF while body aches and joint pain were most common in those with chikungunya fever. Deranged liver function and leukopenia were the most common complications in dengue. Conclusion: Joint-related symptoms (pain and restricted movements) were statistically significant in chikungunya monoinfection. Two patients with DF were died. There was no significant added severity of clinical features and blood investigations in patients with coinfection with dengue and chikungunya compared to those with monoinfections.